BACK-REFERRAL PROGRAM IN THE ERA OF NATIONAL HEALTH INSURANCE AT BALUNG DISTRICT GENERAL HOSPITAL OF JEMBER IN 2017 - Christyana Sandra; Agita Brastila Esti; Eri Witcahyo (Universitas Airlangga, 2019)
Background: In 2014, National Health Insurance Program (BPJS Kesehatan) implemented Back-Referral Program (BRP) to facilitate access to health care for patients with chronic diseases in stable conditions. However, the program did not run well at District General Hospital of Balung which had the lowest back-referral program (6 participants) in 2015-2016.Aim: The study aims to examine the BRP at Balung District General Hospital of Jember in 2017.Methods: This study is designed as qualitative case study. The informants consisted of head of treasury verification, secretary of JKN service controlling, officers of local government’s free care scheme, coordinator of internal and neurological disease, specialists in internal and neurological diseases, officers of Social Security Agency for Health, officers of patient eligibility verification, and participants of Back-Referral Program. The study was conducted from October to December 2017.Results: Results show that the attendance of BPJS Kesehatan officers has no contribution to the services of BPJS Kesehatan in the hospital. Participants also find it difficult to follow the steps of BRP due to unavailability of drugs at primary healthcare centers. Moreover, neurologists have not written any referral recommendation since 2016, so there was no patient admittance.Conclusions: The BRP at Balung District General Hospital did not achieve its target (<5 cases/week). In the contrary, the average number of patients referred to the hospital was 86 patients per week. Balung District General Hospital should implement Standard Operating Procedure for letters signed by responsible physician for patients and evaluate the BRP. Keywords: National Health Insurance, Back-referral program, Hospital, Social security.